Meningitis in Baghdad 1993 – 1998 Part 1: Acute Bacterial Meningitis - Al- Kaisi, Khulood J.; Al- Chaderchi, Abbas A.; Al- Ethawy, Saleh J.; Al- Diwan, Jawad K; Al-Hadithi, Tariq S. (Journal of the Faculty of Medicine Baghdad, 2009)
Background: There is a need for a periodic review of acute bacterial meningitis (ABM) since the pathogens responsible for infection vary with time, geography and patient's age. This study was carried out to describe the epidemiology of different types of meningitis and variables affecting the outcome (improvement, complication and death).Patients and Methods: All the cases of meningitis diagnosed and treated at Ibn- Al-Khateeb Teaching Hospital for the period Jan. 1993 to Dec. 1998 were included in this study. The collected data were age, sex, occupation, date of admission, date of discharge, type of meningitis and outcome of the disease.Results: Out of the total cases, 73.3% were ABM. High rate of ABM was among children < 5 years of age and a significant (p = 0.01) high rate was observed among male (60%) (p = 0.01). Predictors of outcome of meningitis were age, sex, residence, duration of hospitalization and type of meningitis.Conclusion: ABM was predominantly observed in children. The high case fatality rate reported in this study was attributed to the deterioration of health services due to wars and sanctions in 1990s.